2011
DOI: 10.1371/journal.pone.0014493
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Herpesvirus Immune Evasion Strategies to Modify the Immunogenicity of Human Mesenchymal Stem Cell Transplants

Abstract: BackgroundMesenchymal stem cells (MSCs) are multipotent cells residing in the connective tissue of many organs and holding great potential for tissue repair. In culture, human MSCs (hMSCs) are capable of extensive proliferation without showing chromosomal aberrations. Large numbers of hMSCs can thus be acquired from small samples of easily obtainable tissues like fat and bone marrow. MSCs can contribute to regeneration indirectly by secretion of cytokines or directly by differentiation into specialized cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 78 publications
0
21
1
Order By: Relevance
“…Expression of either US6 or US11 resulted in significant suppression of MHC class I surface expression, and facilitated hMSC evasion of recognition by cytotoxic lymphocytes. Interestingly, in contrast to de la Garza-Rodea’s report 93 , expression of US11 also resulted in protection from lysis in co-cultures with NK-92MI cells. However, the mechanism of hMSC evasion from NK cells was not fully elucidated.…”
Section: Strategies To Prolong Msc Persistencecontrasting
confidence: 94%
See 2 more Smart Citations
“…Expression of either US6 or US11 resulted in significant suppression of MHC class I surface expression, and facilitated hMSC evasion of recognition by cytotoxic lymphocytes. Interestingly, in contrast to de la Garza-Rodea’s report 93 , expression of US11 also resulted in protection from lysis in co-cultures with NK-92MI cells. However, the mechanism of hMSC evasion from NK cells was not fully elucidated.…”
Section: Strategies To Prolong Msc Persistencecontrasting
confidence: 94%
“…For example, de la Garza-Rodea et al looked to viruses for inspiration to enable MSCs to evade immune detection. To permanently suppress MHC class I surface expression, they transfected hMSCs with viral immunoevasins from bovine herpes virus type 1, Epstein-Barr virus and human cytomegalovirus (HCMV) 93 . Of these, only the US11 protein from HCMV strongly suppressed hMSC expression of MHC class I.…”
Section: Strategies To Prolong Msc Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Also, the results presented here demonstrating that, at low NK-to-MSC ratios, the ability of NK to kill both transduced and untransduced MSC is diminished, are in agreement with others that showed this same effect, and that both IFN-gamma and IL-10 were involved in the mechanism of regulating NK function [65]. However, this mechanism does not explain the decrease in NK cytotoxicity towards MSC transduced with US 2,3 and 11 at ratios of 20∶1 and 10∶1, and does not concur with a study which demonstrated that down-regulation of MHC-I expression rendered the cells susceptible to NK cells when transplanted in a xenograft model [66]. However, since our results were obtained with in vitro assays and in the other study the results were obtained after in vivo transplantation, it is difficult to directly compare the seemingly conflicting results.…”
Section: Discussionmentioning
confidence: 76%
“…In these studies, cells were also administered intradermally and the numbers of cells administered were of the same order of magnitude, the main differences with our experiments being that the MSCs were of syngeneic origin and that additional MSCs were directly applied onto the surface of the open wound. We used human MSCs, but that was not likely the cause of the difference as our recipients were immunodeficient NOD/SCID mice in which the reduction of the implanted cells over time [42] was similar to that noted by Wu et al [38]. …”
Section: Discussionmentioning
confidence: 99%